Epigenetic Repression of CCDC37 and MAP1B Links Chronic Obstructive Pulmonary Disease to Lung Cancer. Issue 8 (August 2015) - Tessema, Mathewos; Yingling, Christin M.; Picchi, Maria A.; Wu, Guodong; Liu, Yushi; Weissfeld, Joel L.; Siegfried, Jill M.; Tesfaigzi, Yohannes; Belinsky, Steven A.
Abstract : Introduction: Lung cancer and chronic obstructive pulmonary disease (COPD) share environmental risk factors. COPD also increases the risk of lung cancer; however, the molecular mechanisms are unclear. Methods: An epigenome-wide association study of lung tumors and cancer-free lung tissue (CFLT) pairs from non–small-cell lung cancer cases with (n = 18) or without (n = 17) COPD was conducted using the HumanMethylation450 beadchip (HM450K). COPD-associated methylation of top-ranked genes was confirmed in a larger sample set, independently validated, and their potential as sputum-based biomarkers was investigated. Results: Methylation of CCDC37 and MAP1B was more prevalent in lung tumors from COPD than non-COPD cases [54 of 71 (76%) versus 20 of 46 (43%), p = 0.0013] and [48 of 71 (68%) versus 17 of 46 (37%), p = 0.0035], respectively, after adjustment for age, sex, smoking status, and tumor histology. HM450K probes across CCDC37 and MAP1B promoters showed higher methylation in tumors than CFLT with the highest methylation seen in tumors from COPD cases ( p < 0.05). These results were independently validated using The Cancer Genome Atlas data. CCDC37 methylation was more prevalent in sputum from COPD than non-COPD smokers ( p < 0.005) from two cohorts. CCDC37 and MAP1B expression was dramatically repressed in tumors and CFLT from COPD than non-COPD cases, p less than 0.02. Conclusions: The reduced expression of CCDC37 and MAP1B associated with COPD likely predisposes these genes to methylation that in turn, may contribute to lung cancer.